Re-socializing the Vulnerable Brain: Building an Ethically Sustainable Brain Disease Model of Addiction - Kuorikoski, Jaakko; Uusitalo, Susanne (Frontiers in Sociology, 2018)
According to the brain disease model of addiction (BDMA), substance addiction is a chronic, relapsing brain disease. The BDMA is currently influential in informing addiction policy and the development of new treatments, but remains highly controversial across the addiction research community. We draw on resources from philosophy of science and applied ethics to re-examine the methodological and ethical implications of the BDMA and offer a new forward-looking and constructive conceptualization of the BDMA as a heuristic reductionist research hypothesis. We argue that this not only allows a sharper delineation of the empirical shortcomings of the BDMA, but also helps skeptical social scientists appreciate and incorporate the empirical successes of the BDMA to a broader, social understanding of addictions. We apply this view to the ethical implications of the BDMA, especially to the key concept of vulnerability. The BDMA states that it is the brain that has been hijacked by the drug and the brain thus compels the individual to act in ways that are often disastrous for the individual. The proponents of the BDMA ascribe ‘vulnerability’ to multiple levels of organization, such as genes, specific neural systems, the brain, and the person, thus resulting in confusion and highly problematic ethical, social and even legal implications. The BDMA locates the vulnerability firmly within the individual and treats it as a matter of susceptibility to changes in brain chemistry. This may well be a part of the phenomenon, but the kind of vulnerability relevant for understanding and treating addiction is, however, embedded in normativity, as it concerns the agency of individuals with addiction. Agency is not simplistically reducible to the competencies of the individual, but rather it is also constituted in the interactions with their environment.